Criterios para un debido pase a la situación de retiro por la causal de renovación de cuadros en la Policía Nacional del Perú: elementos para una modificación normativa que garantice los fines organizacionales de la institución policial y los derechos fundamentales de oficiales. - Izaguirre Dionicio, Enzo Martin (2022)
The renewal of cadres in the National Police of Peru constitutes a ground contained in article 83 of the Legislative Decree Nº 1149, Law of the career and situation of the personnel of the National Police of Peru, whose purpose is to permanently exclude the police personnel from active service, moving them to the retirement status. Although the law and its regulation, contained in the Supreme Decree Nº 016-2013-IN intend the culminarion of the active service of certain police personnel, the procedure for that objective turns out being substantially detrimental. In that sense, this research seeks to contribute with the procedure for the renewal cadres in the police institution, proposing some guidelines in order to reform Legislative Decree Nº 1149 and its regulation.